Odpowiedzi

Najlepsza Odpowiedź!
  • BiP
  • Rozwiązujący
2010-03-20T15:32:11+01:00
7)2w*(4w-10w-9w-2)=8w^2-20w^2-18w^2-4w=-12w^2-18w^2-4w=-30w^2-4w
6)x*(3x+2x-9)=3x^2+2x^2-9x=5x^2-9x
5)(-1/2a+1/4b-3a*b)*4ab=-2a^2b+ab^2-12a^2b^2
4)(-10gh+20g-30h)*(-0,1gh)=(-10gh+20g-30h)(-1/10gh)=gh-2g^2h+3gh^2
3)(2/3p+3/4p+4/5p+5/6)*60p=40p^2+45p^2+48p^2+50p=133p^2+50p
2)(2,8s*w+6,4s-1,8w)*2,5sw=(28/10sw+64/10s-18/10w)*25/10sw=700/100s^2w^2+1600/100s^2w-450/100sw^2=7s^2w^2+16s^2w-4,5sw^2
1)-1/3*(-5p+1i1/2q+6pq-4/5)=5/3p-1/3*3/2q-2pq+4/15=5/3p-1/2q-2pq+4/15